ANALISIS SELF REGULATED LEARNING MAHASISWA PAI IAIN BATUSANGKAR (STUDI MAHASISWA PAI SEMESTER III ANGKATAN 2017) - Pebrina, Rizki; Putri, Ica Yuliana (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
The main problem in this study is related to student learning styles that are still not optimal, and tend to be teacher centered, and lack of preparation in learning. The purpose of this study is to describe the Self Regulated Learning of PAI IAIN Batusangkar Students in metacognitive aspects, motivation and active behavior. The type of research used is the type of field research (Field Research) with quantitative descriptive methods. Data collection techniques using a questionnaire. The data analysis technique that the author uses in this study is quantitative analysis that is descriptive statistics used to analyze data by describing or describing the data collected. Then present it in the form of a diagram. From the research that has been done, it is obtained that the overall picture of Self Regulated Learning of PAI 2017 Batusangkar IAI Class is classified as high with a percentage of 71.77%. The picture of Self Regulated Learning based on metacognitive aspects obtained a percentage of 67.65% with the category "high", while for the motivation aspect obtained a percentage of 77.03% with the category of "high" and for the description of active behavior obtained a percentage of 70.47% with the category "High" Based on the data obtained it was concluded that Self Regulated Learning of PAI students in semester 3 of 2017 was in the high category.